FILSAFAT DIVINITAS (KEILAHIAN) ATAU TEOLOGI - Armada Riyanto (Jurnal Teologi (Journal of Theology), 2015)
On December 10, 2014, a national seminar discussing the theme "Philosophy of Divinity: Rethinking Theology in the Context of Scientific Discourse, Higher Education and Society" took place in Sanata Dharma University, Yogyakarta. At the seminar, the author presented his ideas regarding the mention of theology as "philosophy of divinity". The author argues that theology that we know as the systematic reflection on faith can be referred as "philosophy of divinity". By tracing the development of theology in history, the author find that the term "divinity" (indonesian translation for keilahian) designates the content of what is now understood as theology. The mention of theology as philosophy of divinity does not eliminate its meaning, let alone the essence. In history of its development, theology always interacted with philosophy. After accountable argument with the historical perspective, the author draws some practical implications of "changing" theology into philosophy of divinity. This article is a further development of the ideas the author presented in the seminar.